2005
DOI: 10.1093/clipsy/bpi014
|View full text |Cite
|
Sign up to set email alerts
|

Intrapersonal, Interpersonal, and Contextual Factors in Engaging in and Responding to Extramarital Involvement

Abstract: Extramarital involvement (EMI) occurs with high prevalence among couples in clinical and community settings, frequently resulting in considerable distress both to participants and their spouses. The field lacks a synthesized review of this literature. Without such a synthesis, it has been difficult for researchers and clinicians to have an understanding of what is and is not known about EMI. This article reviews the large and scattered EMI literature using a framework that encompasses multiple source domains a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
135
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(143 citation statements)
references
References 120 publications
(143 reference statements)
7
135
1
Order By: Relevance
“…Regardless of the type of relationship, gender has been established as the most consistent predictor of EDI (Allen et al, 2005;Blow & Hartnett, 2005b). Across cultures, it has been shown that during marriage more men than women report EDI (Kontula & Haavio-Mannila, 1995;Lewin, 2000;Traeen & Stigum, 1998;Wiederman, 1997).…”
Section: Individual Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Regardless of the type of relationship, gender has been established as the most consistent predictor of EDI (Allen et al, 2005;Blow & Hartnett, 2005b). Across cultures, it has been shown that during marriage more men than women report EDI (Kontula & Haavio-Mannila, 1995;Lewin, 2000;Traeen & Stigum, 1998;Wiederman, 1997).…”
Section: Individual Factorsmentioning
confidence: 99%
“…Regarding online EDI, research has suggested that males are more likely than females to engage in romantic relationships over the internet (Cooper, Delmonic, & Burg, 2000;Wysocki, 1998) and to engage in online sexual behaviors (Luo et al, 2010;Martins et al, 2014). Yet, recent research suggests that the gap between men and women in rates of EDI is narrowing (Adamopoulou, 2013;Brand, Markey, Mills, & Hodges, 2007;Havlicek, Husarova, Rezacova, & Klapilova, 2011;O'Sullivan & Ronis, 2013), particularly in younger cohorts (Allen et al, 2005;Wysocki & Childers, 2011). Despite these attenuated differences, gender is considered an important variable (Andrews et al, 2008;Traeen & Martinussen, 2008), not only to understand the prevalence of EDI, but also of its correlates, which may differ as a function of gender (e.g., Havlicek et al, 2011;Mark et al, 2011).…”
Section: Individual Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In every phenomenon, factors could be categorized into three basic dynamics, that is, predisposing, triggering, and perpetuating factors. A comprehensive review done by Allen et al (2005) emerged six factors that reflect the stages of extramarital involvement, that is, predisposing, approach, precipitating, maintenance, discovery or disclosure, and response. These defined factors that are along the dimensions of the individual (offending party and the offended), marital relationship, and external context (extramarital partner and relationship, workplace, peer, and culture) thoroughly illustrate the development of the EMR from pre to post involvement.…”
Section: Dynamics Of Factors In Literaturementioning
confidence: 99%
“…The bulk of similar studies focused more on the couple relationship and opportunities and less to almost none on the familial relationship (see Allen et al, 2005;Drigotas & Barta, 2012). In a collectivist culture like the Philippines, the family is a significant influence in decision making.…”
Section: Triggering Factorsmentioning
confidence: 99%